Mathematics Intervention Supporting Allen, a Latino EL: A Case Study - Marialuisa Di Stefano; Kristy Litster; Beth L. MacDonald (MDPI AG, 2017)
This research discusses a single case study of a first-grade Latino English Learner (EL) student, Allen (pseudonym), from a larger inquiry-based intervention on inversion and mental reversibility development. The purpose of this case study was to develop a better understanding of the relationship between Allen's English language proficiency and his ability to solve inversion and compensation mathematics tasks. The integration of multiple paradigms confronting radical constructivism and sociocultural theory of learning via culturally relevant pedagogy provided us with a multi-faceted set of perspectives in understanding the interconnection between Allen's cultural and linguistic background and his development of algebraic reasoning. Through conceptual and retrospective analyses, we found that Allen's language features are highly correlated with the development of his thinking strategies and his ability to solve mathematics tasks. Implications of this study include the development of teaching strategies that address critical issues in mathematics, such as the individual differences of learners, specifically ELs from Latino background. We suggest further research is needed in the field of language acquisition and access to STEM related concepts.